Absorption, Pharmacokinetics, and Urinary Excretion of Pyridines After Consumption of Coffee and Cocoa‐Based Products Containing Coffee in a Repeated Dose, Crossover Human Intervention Study. Issue 18 (20th August 2020) - Bresciani, Letizia; Tassotti, Michele; Rosi, Alice; Martini, Daniela; Antonini, Monica; Dei Cas, Alessandra; Bonadonna, Riccardo; Brighenti, Furio; Del Rio, Daniele; Mena, Pedro
Abstract : Scope: The present study assesses the absorption, pharmacokinetics, and urinary excretion of coffee pyridines and their metabolites after daily regular exposure to specific dosages of coffee or cocoa‐based products containing coffee (CBPCC), considering different patterns of consumption. Methods and results: In a three‐arm, crossover, randomized trial, 21 volunteers are requested to randomly consume for 1 month: one cup of espresso coffee per day, three cups of espresso coffee per day, or one cup of espresso coffee plus two CBPCC twice per day. The last day of the one‐month treatment, blood and urine samples are collected for 24 h. Trigonelline, N ‐methylpyridinium, N ‐methylnicotinamide, and N ‐methyl‐4‐pyridone‐5‐carboxamide are quantified. Trigonelline and N ‐methylpyridinium absorption curves and 24‐h urinary excretion reflect the daily consumption of different servings of coffee or CBPCC, showing also significant differences in main pharmacokinetic parameters. Moreover, inter‐subject variability due to sex and smoking is assessed, showing sex‐related differences in the metabolism of trigonelline and smoking‐related ones for N ‐methylpyridinium. Conclusion: The daily exposure to coffee pyridines after consumption of different coffee dosages in a real‐life setting is established. This data will be useful for future studies aiming at evaluating the bioactivity of coffee‐derived circulating metabolites in cell experiments, mimicking more realistic experimental conditions. Abstract : The daily exposure to coffee pyridines after consumption of different coffee dosages in a real‐life setting is established. These data will be useful for future studies aiming at evaluating the bioactivity of coffee‐derived circulating metabolites in cell experiments, mimicking more realistic experimental conditions.